THE RELATIONSHIP OF COUPING MECHANISM WITH THEFAMILY STRUCTURE AMONG CHILDREN WITH MENTAL RETARDATION ATBOGOR: HUBUNGAN MEKANISME KOPING DENGAN TINGKAT STRES ORANG TUA PADA ANAK YANG RETARDASI MENTALDI KOTA BOGOR - Al Muhajirin; Yoyo Haryono (Wijaya Husada, 2018)
Coping mechanisms in the elderly include adaptive and maladaptive coping. Adaptive coping can help a person to deal effectively with stressful events and minimize the problems they experience. While maladaptive coping causes stress for individuals and families. According to the Extraordinary School Statistics Data in 2015 West Java ranked first with the most mental retardation children in Indonesia. To find out the relationship of coping mechanisms with the stress level of parents in children who have mental retardation in Bogor City. This type of research is quantitative analytic. This research was conducted in the Bogor City Region with a sample of 35 children using a total sampling technique. The instruments used were questionnaires while the data analysis techniques were using univariate and bivariate analyzes. Based on the statistical test using the chi square obtained P value = 0.955, it was concluded that Ho is accepted and Ha is rejected, meaning there is no relationship between coping mechanisms with stress levels of parents towards mental retradation children in BogorCity.